Roles of CfxA, CfxB, and external electron acceptors in regulation of ribulose 1,5-bisphosphate carboxylase/oxygenase expression in Rhodobacter sphaeroides. - Hallenbeck, P L (1990)
The Rhodobacter sphaeroides genome contains two unlinked genetic regions each encoding a series of proteins involved in CO2 fixation which include phosphoribulokinase (prkA and prkB) and ribulose 1,5-bisphosphate carboxylase/oxygenase (rbcLS and rbcR) (P. L. Hallenbeck and S. Kaplan, Photosynth. Res. 19:63-71, 1988; F. R. Tabita, Microbiol. Rev. 52:155-189, 1988). We examined the effect of CO2 in the presence and absence of an alternate electron acceptor, dimethyl sulfoxide, on the expression of rbcR and rbcLS in photoheterotrophically grown R. sphaeroides. The expression of both rbcR and rbcLS was shown to depend on the CO2 concentration when succinate was used as the carbon source. It was also demonstrated that CO2 fixation is critical for photoheterotrophic growth but could be replaced by the alternative reduction of dimethyl sulfoxide to dimethyl sulfide. Dimethyl sulfoxide severely depressed both rbcR and rbcLS expression in cells grown photoheterotrophically at CO2 concentrations of 0.05% or greater. However, cells grown photoheterotrophically in the absence of exogenous CO2 but in the presence of dimethyl sulfoxide had intermediate levels of expression of rbcL and rbcR, suggesting partially independent control by limiting CO2 tension. We also present evidence for the existence of two gene products, namely, CfxA and CfxB, which are encoded by genes immediately upstream of rbcLS and rbcR, respectively. Strains were constructed which contained null mutations in cfxA and/or cfxB. Each mutation eliminated expression of the linked downstream rbc operon. Further, studies utilizing these strains demonstrated that each form of ribulose 1,5-bisphosphate carboxylase/oxygenase plays an essential role in maintaining the cellular redox balance during photoheterotrophic growth at differing CO2 concentrations.